PTU-066 Non-invasive assessment of systemic haemodynamics to determine variceal bleeding risk in cirrhotic patients. (23rd September 2015) - Rye, K A; Mortimore, G; Austin, A; Freeman, J
Abstract : Introduction: Variceal bleeding is one of the most severe complications of portal hypertension. Universal endoscopic variceal screening is recommended and primary prophylaxis given based on oesophageal variceal size. Risk of bleeding also relates to other factors such as portal pressure, liver disease severity, and red wale markings at endoscopy. Currently there is no non-invasive way of measuring portal pressure or bleeding risk. The aim of this study was to evaluate whether non-invasive assessment of systemic haemodynamics in cirrhosis can identify bleeding risk in portal hypertension. Methods: We studied 29 cirrhotic patients. Systemic haemodynamics and baroreceptor sensitivity (BRS) were assessed non-invasively using the Finometer® (TNO instruments, Amsterdam), and analysed with Beatscope® software. Spontaneous BRS was assessed by studying the relationship between inter-beat variability and beat-to-beat changes in systolic blood pressure. Portal pressure was assessed by measurement of the hepatic venous pressure gradient (HVPG). Gastroscopy assessed variceal size, Japanese score and 1-year probability of bleeding according to the NIEC index. Results: 69% male, median age 47 (42–55) years, Child-Pugh (CP) score 6 (Class A 18, Class B 10, Class C 1) and MELD 10 (8–13). 90% alcoholic cirrhosis, 66% abstinent. HVPG correlated positively with variceal size (r=0.64, p<0.001), and all measures of variceal bleeding risk (Abstract 066 ). Significant positive correlations were seen with CI, HR and SVR and variceal bleeding risk, while a significant negative correlation was seen with BRS and bleeding risk. HVPG correlated positively with both CI (r=0.53, p=0.005) and HR (r=0.62, p<0.001) and negatively correlated with BRS (r=−0.69, p<0.001). BRS correlated negatively with HR (r=−0.56, p=0.002). Conclusion: Non-invasive assessment of systemic haemodynamics in cirrhosis may be useful in predicting HVPG and bleeding risk from oesophageal varices. This study highlights that other factors such as baroreceptor sensitivity are important in determining portal pressure and bleeding risk and may open up potential new treatment options.